2017
DOI: 10.1177/0972150917692169
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Trade-off Between Social Outreach and Financial Efficiency: Evidence from Micro-finance Institutions in South Asia

Abstract: The micro-finance institutions (MFI) have been successfully operating for poverty alleviation. The recent turmoil in financial sustainability of major MFIs worldwide has raised the question of whether trade-off exists: Financial performance cannot be achieved without sacrificing the main objective—social outreach. This article examines the presence of such a trade-off by examining the empirical evidence from 127 South Asian MFIs over 2009–2013. The findings of this article reveal that MFIs have neutral trade-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(56 reference statements)
2
12
1
Order By: Relevance
“…Thus, the higher the profitability, the easier it will be for banks to carry out their social functions. This finding contradicted with the previous studies (Kipesha & Zhang, 2013;Abdulai & Tewari, 2017;Huq et al, 2017) that concluded the negative connection between Return on Assets (ROA) with "outreach", one of the indicator for the social function. Thus, this research concluded that the two aims of MFIs could be achieved at the same time, and there is no trade-off between profitability and the achievement of social function for rural banks.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…Thus, the higher the profitability, the easier it will be for banks to carry out their social functions. This finding contradicted with the previous studies (Kipesha & Zhang, 2013;Abdulai & Tewari, 2017;Huq et al, 2017) that concluded the negative connection between Return on Assets (ROA) with "outreach", one of the indicator for the social function. Thus, this research concluded that the two aims of MFIs could be achieved at the same time, and there is no trade-off between profitability and the achievement of social function for rural banks.…”
Section: Resultscontrasting
confidence: 70%
“…The dependent variable in this research is social performance, proxied by the number of clients (Schreiner, 2002;Huq et al, 2017). The independent variables in the model are profitability which proxied with Return on Assets, the regulation which proxied with Capital Adequacy Ratio and competition which proxied with the prime lending rate (De Cloet & Moyaert, 2014;Gwasi & Ngambi, 2014;Axmann, 2015;Johnson, 2015;Quayes, 2015).…”
Section: Variable and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster is nonetheless associated with a higher operation interest rate than of Cluster 2, possibly due to the need to cover possible losses, because these clients are considered at high risk. This group of clients can be defined as the poorest in the CrediAmigo program (Huq et al , 2017).…”
Section: Methods and Estimation Resultsmentioning
confidence: 99%
“…This type of client can take out a loan with a traditional bank. On the other hand, Huq et al . (2017) wondered whether microfinance programs are really helping the very poor; they argued that microfinance programs can serve poor people, but not the poorest.…”
Section: Introductionmentioning
confidence: 99%